Chemical and Antioxidant Charaterization of Native Corn Germplasm from Two Regions of Costa Rica: A Conservation Approach - Randall Syedd-León; Rafael Orozco; Víctor Álvarez; Yendry Carvajal; Gerardo Rodríguez (International Journal of Food Science)
The cultivation of native corn has decreased in favor of the cultivation of improved commercial corn varieties. This study seeks to evaluate the antioxidant and antibacterial potential of 36 samples of native corn germplasm from the Brunca (BR) and Chorotega (CR) regions of Costa Rica. The main parameters of comparison were the composition of antioxidant compounds, antiradical activity, and microbicidal effect. The total amount of polyphenols in the germplasm (120 mg GAE/100 g d.w.) was not related to the regions from which the samples were obtained. The overall average for antioxidant capacity was 21.20 μmol TE/g d.w. Accessions from the CR region had higher antioxidant capacity. Anthocyanin content was higher in purple accessions and undetectable in white germplasm. Antioxidant capacity was statistically related to polyphenols content (r=0.714, p<0.01). The most promising corn accessions in terms of nutraceutical value came from the CR region.